Antara Ideal dan Utopis dalam Cerpen “Dongeng Tarka dan Sarka”:Telaah Konsep Kebersamaan Jean-Luc Nancy - M. Hafidzulloh SM (Badan Pengembangan dan Pembinaan Bahasa, 2020)
The discourse about human existence in the world is a form of dasein communality that forms a certain group. The existence of groups then brings human life in the dimension of Being-In-Common. With the concept of Being-In-Common the subject continues to move and proceed towards an ideal situation. This situation become to the concept of Literary Utopia, where the subjects lives continued to share in togetherness. This part of the meaning of life is possible to lead in ideal conditions, a fantasy of a better life for the future with a sense of brotherhood as the key. Meanwhile, the ideal situation is a condition where the community goes to a dimension that has not yet been perfectly translated, so that a series of processes of division into a utopian step. It's no longer towards the ideal, but the mechanism that makes the lives of subjects share meaning. This condition then becomes the navigation’s subject determined in his ideal life, because if there is no dialectics, then life will be finished and no part of the expected meaning. Short story